Antennal sensilla of some forensically important flies in families Calliphoridae, Sarcophagidae and Muscidae - Sukontason K. (2014)
Antennal sensilla of some forensically important fly species in the families Calliphoridae (Chrysomya megacephala, Chrysomya rufifacies, Chrysomya nigripes and Lucilia cuprina), Sarcophagidae (Parasarcophaga dux) and Muscidae (Musca domestica) were studied using scanning electron microscopy. Five types of sensilla were observed: trichoid, basiconic, coeloconic, styloconic and sensory pit. Only trichoid sensilla are found on the scape of the antenna, while both trichoid and styloconic sensilla are located on the antennal pedicels of all species studied. Basiconic sensilla are the most numerous of the sensilla found on the antennae of both sexes of all fly species studied and are comprised of two subtypes: large and small basiconic sensilla. Coeloconic sensilla are characterized by short pegs, with either grooved or smooth surfaces, that are sunken into deep depressions. No marked difference was observed in the number, morphological structure or distributional pattern of any of the sensilla among the species studied, with the exception of there being more numerous sensory pits detected in female P. dux compared to the other species. The suggested function of each antennal sensillum was based on comparison with results of other investigations on similar sensilla. © 2004 Elsevier Ltd. All rights reserved.